Quantitative ethnobotanical appraisal of plants used by inhabitants of Jelar Valley, Dir Upper, Northern Pakistan - Ullah, Shariat; Badshah, Lal; Hussain, Wahid; Hussain, Iqtidar; Ali, Asghar (Ethnobotany Research and Applications, 2023)
Background: Due to the lack of primary health facilities and poor economic situation, the traditional use of plants for curing diseases is very common in rural areas of developing countries across the globe. The present study aimed to explore people-plant interaction and the conservation status of Jelar Valley, during 2014-2017. Objectives: The main goals of this research were; to enlist the medicinal flora; to gather indigenous knowledge concerning the medicinal plants; to assess the conservation status of the medicinal flora area. Methods: To collect information on ethno-botanical uses of plant species, a semi- structure questionnaire was prepared, and information was collected from local knowledgeable peoples of the area including male and female as well from local people. A total of 135 informants were interviewed regarding ethno-medicinal uses of the plants found in the area. The collected plants were classified into various used categories on the basis of information on their ethno-botanical uses. The relative frequency of citation, family importance values and conservation status were also calculated. Results: In the present study, checklist of 83 plants was prepared and also determined its conservation status. The results revealed that of the 83 medicinal species (62.7%) were herbs, (21.7%) were trees and the remaining (15.7%) species belonged to shrubs. The results showed that mostly the species were used as a whole plant (21.7%), followed by leaves (25.3%), leaves and fruit (9.6%), Based on Family Importance Value (FIV) the best represented used family was Lamiaceae (91.11 %), followed by Asteraceae, while the highest Relative Frequency Citations was recorded for Mentha longifolia (0.266) followed by Olea ferruginea (0.259). The conservation status of medicinal flora revealed that Melia azedarach was found endangered, 35 (42%) species were rare, 15 (18%) species infrequent and 32 (39%) species were recorded as vulnerable in the area. Following the International Union for Conservation of Nature criteria 2001 for conservation none of the population was declared in the dominant category. Conclusion: The study showed that the area has a great diversity of plants used for different ailments. The plants' utilization and unsustainable use of plants increase day by day for different purposes. The diseases are increasing day by day; they may cause a great threat to the flora of the Valley. The survey aims to make people aware of valuable plants and to protect them from extinction. The old people are aware of the accurate knowledge of medicinal plants and are needed to preserve this knowledge for the next generation. Keywords: Ethno-botanical, conservation, Jelar, Dir Upper, Pakistan